Introduction to microcontroller programming for power electronics control applications : coding with MATLAB and Simulink /: coding with MATLAB and Simulink. (2021) - Rossi, Mattia; Toscani, Nicola; Mauri, Marco; Dezza, Francesco Castelli
No abstract available